Impact of irrigation on vulnerability of winter wheat under extreme climate change scenario: a case study of North China Plain - Yulian Gao; Lin Wang; Yaojie Yue (Frontiers in Sustainable Food Systems, 2024)
An inadequate understanding of the impacts of adaptation countermeasures tends to exaggerate the adverse effects of climate change on agricultural systems. Motivated by proposing reasonable climate change adaptation countermeasures, the present study applied the EPIC model to quantify the impacts of climate change and irrigation changes with future socioeconomic development on agricultural production. Winter wheat yield losses using dynamic irrigation parameters in the North China Plain (NCP) from 2010 to 2099 under a scenario coupling climate change and future socioeconomic development (RCP8.5-SSP3), and those under an extreme climate change scenario (RCP8.5), were simulated. Results show that EPIC model demonstrates superior performance in simulating winter wheat yields in NCP (RMSE = 12.79 kg/ha), with the distribution of simulated and observed yields is relatively consistent. The winter wheat yield loss in the NCP was high in the south and low in the north. The yield loss rate of winter wheat was 0.21 under the RCP8.5-SSP3 scenario, compared with 0.35 under the RCP8.5 scenario, indicating a superior climatic adaptation of irrigation. However, under the RCP8.5-SSP3 scenario, the yield loss rate increased from 0.17 in the near term to 0.26 in the long term, implying the benefits of irrigation will be diminished with long-term climate change. It is noteworthy that yield improvement was facilitated by irrigation in part of the NCP (accounting for 14.6% area), suggesting that irrigation may lead to an increase in winter wheat yields in some regions even under extreme climate change conditions. This study highlights the significance of quantitatively revealing the benefits and limitations of adaptive countermeasures which could assist in enhancing climate change adaptation while preserving a sustainable agricultural system.